The Courts, The Ballot Box, and Gay Rights : How our Governing Institutions Shape the Same-Sex Marriage Debate - Mello, Joseph (Book collections on Project MUSE., 2016)
"In its analysis of the same-sex marriage issue, The Courts, the Ballot Box, and Gay Rights provides insights that illuminate some of the most salient rights-based issues of our time - including affirmative action, abortion, immigration, and drug policy. The book offers a new way of understanding how such issues are decided, and how important context can be in determining the outcome."--Jacket